How Do Banks React to Catastrophic Events? Evidence from Hurricane Katrina - Schüwer, Ulrich; Lambert, Claudia; Noth, Felix (Review of Finance, 2019)
Abstract This paper explores how banks react to an exogenous shock caused by Hurricane Katrina in 2005, and how the structure of the banking system affects economic development following the shock. Independent banks based in the disaster areas increase their risk-based capital ratios after the hurricane, while those that are part of a bank holding company on average do not. The effect on independent banks mainly comes from the subgroup of highly capitalized banks. These independent and highly capitalized banks increase their holdings in government securities and reduce their total loan exposures to non-financial firms, while also increasing new lending to these firms. With regard to local economic development, affected counties with a relatively large share of independent banks and relatively high average bank capital ratios show higher economic growth than other affected counties following the catastrophic event.